Validation of the Career Exploration Survey-Revised (CESR) Questionnaires among Secondary School Students in Malaysia - Shukree Yusof; Ahmad Jazimin Jusoh (International Journal of Education, Information Technology, and Others, 2023)
The validity and reliability of Career Exploration Service-Revised (CESR) questionnaires were tested in a pilot study. The objective of the study was to find out how reliable the various parts of the questionnaires were. There were 5 experts and 35 senior high school students involved in this study. The instrument was distributed to students in grades four and higher at two secondary schools in the Hulu Terengganu region. The study participants were students who have already been chosen. Students were chosen to participate in the study from a broader pool of applicants whose characteristics were similar to those of the final study participants. This was done to gauge the extent to which the students trusted the various parts of the instrument. The validity analysis shows that the items are spot-on, allowing the research to proceed. All items on the Self-Exploration sub-construct of the first sub-construct were trustworthy, as shown by high values for the corresponding CESR reliability coefficients.